Pengaruh Daya Tarik Wisata Terhadap Kepuasan Pengunjung di Piaynemo Kabupaten Raja Ampat, Papua Barat Daya - Rumbino, Silvia Gloria; Safaruddin, Safaruddin (Civiliza Publishing, 2025)
Piaynemo Island is located in the West Waigeo district, Raja Ampat Regency, Southwest Papua. Often referred to as